2002
DOI: 10.1200/jco.2002.20.6.1668
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Drug Targeting: Phase I Evaluation of Polymer-Bound Doxorubicin

Abstract: The recommended PK2 dose is 120 mg/m(2), administered every 3 weeks by IV infusion. Liver-specific doxorubicin delivery is achievable using galactosamine-modified polymers, and targeting is also seen in primary hepatocellular tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
197
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(201 citation statements)
references
References 25 publications
3
197
0
1
Order By: Relevance
“…This conjugate was designed (Duncan et al, 1983(Duncan et al, , 1986 to target the asialoglycoprotein receptor present on normal hepatocytes and hepatocellular carcinoma with the hope of improving treatment of primary and secondary liver cancer. Liver targeting of this conjugate has been verified by clinical gamma camera imaging (Seymour et al, 2002).…”
Section: XVIImentioning
confidence: 88%
See 1 more Smart Citation
“…This conjugate was designed (Duncan et al, 1983(Duncan et al, , 1986 to target the asialoglycoprotein receptor present on normal hepatocytes and hepatocellular carcinoma with the hope of improving treatment of primary and secondary liver cancer. Liver targeting of this conjugate has been verified by clinical gamma camera imaging (Seymour et al, 2002).…”
Section: XVIImentioning
confidence: 88%
“…In a Phase I trial, PK2 was shown to produce significant targeting to both normal liver and hepatic tumours with partial clinical responses (Seymour et al, 2002). A Phase II evaluation of PK2 in hepatocellular carcinoma is planned.…”
Section: XVIImentioning
confidence: 99%
“…Other phase I trials with polymeric drug conjugates based on N-(2-hydroxypropyl)methacrylamide copolymers bound to doxorubicin and paclitaxel have been performed (Muggia, 1999;Vasey et al, 1999;Seymour et al, 2002). Vasey et al (1999) showed that PK1 (doxorubicin covalently bound to N-(2-hydroxypropyl)-methacrylamide) decreases doxorubicin DLTs, maintained antitumour efficacy, and demonstrated no polymer-related toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…N-isopropylacrylamide) (Tomer and Florence, 1993;Shah et al, 1997;Soppimath et al, 2001;Jeong et al, 2002), polymethacrylamides (e.g. N-(2-hydroxypropyl) methacryiamide, HPMA) (Kopecek et al ., 1991;Oupicky etal., 2000;Kasuya et al, 2001;Seymour et al, 2002;Stastny et al, 2002) etal., 1998b;Kajihara etal., 2001), and cellulose derivatives (Khan et al, 2000)_ These polymers have been used successfully in bioadhesives (Peppas and Mongia, 1997;Clausen and Bemkop-Schnurch, 2001;Cuna et al, 2001), pH-(Orienti et al, 2000Soppimath et al, 2001), thermo- (Jeong et al, 2002), magnetic-(Dutta et aL, 1995 and photo-responsive (Tomer and Florence, 1993) delivery systems, particulate carders (Orienti et al, 1992;Langer et al, 1997;Wang et al, 1999;Dickinson et al, 2001;Ahlin et al, 2002), drug polymer conjugates (Katre, 1993;Shah et al, 1997;Kasuya et al, 2001), oral controlled-release systems (Junginger et al, 1989;Khan et al, 2000;Streubel et al, 2002), site-specific delivery systems (Khan et al, 2000;Seymour et al, 2002), implantable devices (Diaz et al, 1982), transdermal/topical (Seki et al, 1991;Kajihara et al, 2001;Rafiee-Tehrani et al, 2001), and ophthalmic (Davies et al, 1991;La...…”
Section: Non-biodegradable Polymersmentioning
confidence: 99%